Gender Differences of NLRP1 Inflammasome in Mouse Model of Alzheimer's Disease - Zhang, Jinghang; Pei, Lihong; Zang, Dan; Xue, Yun; Wang, Xiaohui; Chen, Yiyang; Li, Jinsong; Yu, Jian; Gao, Qingzu; Di, Wenyu; Cui, Chaochu; Su, Wei; et al. (Frontiers in Aging Neuroscience, 2020)
Background: The incidence and symptoms of Alzheimer’s disease (AD) have significant gender differences, but its mechanisms are not completely understood. Recent studies showed that NLRP1 inflammasome was markedly overexpressed in females under some other pathological states such as nodular melanoma. Whether NLRP1 signals are also expressed with a gender difference in AD has not been elucidated. This study was designed to investigate the expressions of NLRP1 signals including NLRP1, Capase-1 and IL-1β in brains of different sexual APP/PS1+/- mice. Methods: 30-week-old male and female APP/PS1+/- mice were used in this study. Amyloid-β (Aβ) plaques were stained with Congo red dye and cell apoptosis in brains was detected by TUNEL staining. The expressions of NLRP1, Capase-1 and IL-1β were measured by immunofluorescent staining and Western-blotting assay. RESULTS: The numbers of Aβ plaques in cortex and hippocampus and neuronal apoptosis in cortex of female APP/PS1+/- mice increased 4 and 2 folds than that in males respectively (P<0.001). The average size of Aβ plaques also became larger from 1920.44 m2 to 3527.11m2 in the cortex, and 1038.55 m2 to 1931m2 in hippocampus of male and female APP/PS1+/- mice (P<0.001, P<0.01). More interestingly, expressions of NLRP1, Caspase-1 and IL-1β were markedly increased in cortex of female APP/PS1+/- mice as compared with males. Conclusions: These findings show that NLRP1 signals are highly expressed in female APP/PS1 transgenic mice than males, which may be related to the gender differences of AD.